Periodontitis Salivary Microbiota Aggravates Ischemic Stroke Through IL-17A - Chen, Yan-Lin; Bai, Lan; Dilimulati, Dilirebati; Shao, Shuai; Qiu, Che; Liu, Ting; Xu, Shuo; Bai, Xue-Bing; Du, Lin-Juan; Zhou, Lu-Jun; Lin, Wen-Zhen; Meng, Xiao-Qian; et al. (Frontiers in Neuroscience, 2022)
Although epidemiological studies suggest that periodontitis is tightly associated with ischemic stroke, its impact and mechanism on stroke are poorly understood. Recent studies show alteration in gut microbiota composition influences the outcomes of ischemic stroke, in the state of periodontitis, many oral pathogenic bacteria in the saliva are swallowed and transmitted to the gut. However, the role of periodontitis microbiota in the pathogenesis and progression of ischemic stroke is unclear. Therefore, we hypothesized that the periodontitis salivary microbiota influences the gut immune system and aggravates ischemic stroke. Mice receiving gavage of periodontitis salivary microbiota showed significantly worse stroke outcomes. And these mice also manifested more severe neuroinflammation, with higher infiltration of inflammatory cells and expression of inflammatory cytokines in the ischemic brain. More accumulation of Th17 cells and IL-17+ γδ T cells were observed in the ileum. And in Kaede transgenic mice after photoconversion, migration of CD4+ T cells and γδ T cells from the ileum to the brain was observed after stroke. Further, the worse outcome was abolished in the IL-17A knockout mice. These findings suggest that periodontitis salivary microbiota increased IL-17A-producing immune cells in the gut, likely promoted the migration of these cells from the gut to the brain, and subsequently provoked neuroinflammation after ischemic stroke. These findings have revealed the role of periodontitis in systemic disease through the gut and provide new insight into the worse outcome of stroke coexisting with periodontitis in clinical trials.